Design Analysis of Airport Runway Pavement Overlay using FAARFIELD 2.1 (Case Study: Fatmawati Soekarno Airport, Bengkulu) - Hermawan, Antony; Aulia Sari, Yusra (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2025)
The design and upkeep of airport pavements are essential for guaranteeing safe and efficient air travel. This study assesses the overlay thickness specifications for the Fatmawati Soekarno Airport runway utilizing FAARFIELD 2.1, a pavement design software created by the Federal Aviation Administration (FAA). The evaluation relies on primary and secondary data, encompassing Pavement Condition Index (PCI) analysis, Dynamic Cone Penetration (DCP) tests, and estimates of aircraft traffic. The FAARFIELD methodology uses layered elastic and finite element analysis to simulate pavement performance under escalating load requirements. The findings demonstrate that for STA 0+000 to 1+800, with a subgrade bearing capacity (CBR) of 6%, the necessary overlay thickness is 51mm (5cm) of Hot Mix Asphalt (HMA). Likewise, for STA 1+800 to 2+250, with a subgrade CBR of 10%, the overlay thickness is maintained at 51mm (5cm). The design considers anticipated aircraft traffic expansion over 20 years while retaining the pavement's structural integrity. This study demonstrates the efficacy of FAARFIELD in enhancing overlay designs for airport pavements, hence improving maintenance strategies for aviation infrastructure.